1998
DOI: 10.1021/bi980195b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Near-Infrared Light on the S2-State of the Manganese Complex of Photosystem II from Synechococcus elongatus

Abstract: The Mn cluster of Photosystem II (PSII) from Synechococcus elongatus was studied using EPR. A signal with features between g = 5 and g = 9 is reported from the S2-state. The signal is attributed to the manganese cluster in a state with a spin 5/2 state. Spectral simulations of the signal indicate zero field splitting parameters where the |E/D| was 0.13. The new signal is formed by irradiating PSII samples which contain the spin = 1/2 S2-state using 813 nm light below 200 K. This effect is attributed to a spin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
75
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 44 publications
11
75
0
1
Order By: Relevance
“…37), our preparation contains all function relevant components of the electron donor and acceptor sides with highest degree of preservation. The isolated PS II shows the highest rate of oxygen evolution reported so far, which is in line with a clear multiline signal obtained from EPR measurements before, indicating a functional manganese cluster (38). High rates of oxygen evolution, up to 4500 M O 2 per mg of Chl and per hour, have also been reported from another PS II preparation of the same organism (41); however, this preparation still contains many contaminating proteins making it unsuitable for structural studies.…”
Section: Discussionsupporting
confidence: 87%
“…37), our preparation contains all function relevant components of the electron donor and acceptor sides with highest degree of preservation. The isolated PS II shows the highest rate of oxygen evolution reported so far, which is in line with a clear multiline signal obtained from EPR measurements before, indicating a functional manganese cluster (38). High rates of oxygen evolution, up to 4500 M O 2 per mg of Chl and per hour, have also been reported from another PS II preparation of the same organism (41); however, this preparation still contains many contaminating proteins making it unsuitable for structural studies.…”
Section: Discussionsupporting
confidence: 87%
“…Since the g = 4.1 signal formed by near IR illumination relaxes back to the multiline signal at 200 K, the near IR component of broad light sources is not thought to be responsible for the g = 4.1 signal observed after illumination at 200 K. The near IR-induced conversion from multiline signal to g = 4.1 signal takes place via an intermediate S ‡ 5/2 spin state characterized by EPR signals at g = 6 and g = 10, which can be trapped by illumination at about 65 K (Boussac et al 1998b). Similar intermediate signals at g = 5-9 have been observed in cyanobacteria (Boussac et al 1998a), although the near IRinduced g = 4.1 signal has not.…”
Section: S 2 State Signalssupporting
confidence: 73%
“…Another previously observed Q-band signal, with features at about g = 4.3 and g = 4.1, was identified as the S 2 state g = 4.1 signal, leading to the suggestion that the signal arose from an S = 3/2 state (Smith et al 1993;Smith and Pace 1996); however, the identity of this signal has been called into question (Haddy et al 2004). The X-band g = 4.1 signal was thought not to form in cyanobacterial PSII (McDermott et al 1988;Boussac et al 1998a), however, it was recently shown that its presence correlates with the cytochrome c 550 (PsbV) content of the preparation (Lakshmi et al 2002).…”
Section: S 2 State Signalsmentioning
confidence: 99%
“…After the S 2 -multiline signal was recorded (spectrum c of Figure 8B), the sample was further illuminated by a 820-nm light at 50 K in the EPR cavity. This near-infrared illumination has been shown to convert the spin ) 1 / 2 S 2 -multiline signal state into an S g 5 / 2 spin state characterized by signals around g ) 9 in cyanobacteria (56). Spectrum d of Figure 8B is the difference signal of the before-minus-after 820-nm illumination and corresponds to the S 2 -multiline signal, which disappeared upon near-infrared illumination.…”
Section: Ftir Spectra Of P 680mentioning
confidence: 94%